Accurate First‐Principles Treatment of the High‐Temperature Cubic Phase of Hafnia. Issue 10 (6th June 2022) - Bichelmaier, Sebastian; Carrete, Jesús; Nelhiebel, Michael; Madsen, Georg K. H.
Abstract : HfO2 is an important high‐ k dielectric and ferroelectric, exhibiting a complex potential energy landscape with several phases close in energy. It is, however, a strongly anharmonic solid, and thus describing its temperature‐dependent behavior is methodologically challenging. An approach based on self‐consistent, effective harmonic potentials (EHP) to study the potential energy surface (PES) of anharmonic materials is proposed. The introduction of a reweighting procedure enables the usage of unregularized regression methods by efficiently utilizing the information contained in every data point obtained from density functional theory. The approach is detailed and tested on the example of the high‐temperature cubic phase of HfO2 . It is demonstrated how the correction term for the deviation between the EHP and the true PES can be calculated directly from the same sampling used for determining the EHP. The calculated temperature‐dependent physical properties are in agreement with existing experimental data, thereby opening for the predictive treatment of HfO2 over a wide temperature range. Abstract : A standard harmonic approximation predicts that cubic hafnia (c‐HfO2 ) is mechanically unstable. To correctly reproduce its stability at high temperatures, the potential energy surface is sampled to produce an effective harmonic potential that capture the correct statistics of nuclear motion. The same sampling is used to obtain the correction term for the deviation of the harmonic potential and the true potential.